Influence of basic research investment on corporate performance: Exploring the moderating effect of human capital structure. Issue 8 (12th September 2019) - Song, Malin; Pan, Xiongfeng; Pan, Xianyou; Jiao, Zhiming
Abstract : Purpose: The purpose of this paper is to add to the existing research about how corporate performance is influenced by their basic research (BR) investment. On this basis, the authors examined the moderating effect of human capital structure (HCS) on the relationship between BR investment and corporate performance. Design/methodology/approach: Hypotheses were tested using static and dynamic models to analyze a large-scale data of Chinese A-share listed companies. Findings: This study provides empirical evidence that contributes to the research about how private BR investment influences corporate performance in the digital age. In addition, human resource is an important dynamic ability for enterprise development. Based on the dynamic capability theory, further research finds that the human resources practice on the knowledge stock can enhance the company's dynamic capability, thereby enhancing the company's core competitiveness. Research limitations/implications: The results may be affected by the context of the data set. This study considers the influence of private research investment type on corporate performance, further studies considering the influence of specific contextual variables, such as corporate industry differences, could yield richer insights that would help validate the results of this study. Practical implications: This study provides useful information for managers. As well as increasing the investment in the BR of enterprise and creating the necessary conditions to increase the competitiveness of enterprise, they should strive to adjust the structure and quality of researchers involved in BR projects. Originality/value: This research contributes to the enterprise's BR investment and the management of human capital resource. It points that the investment of BR positively influences the corporate performance. In addition, the increasing of high-skilled labor's proportion positively promotes the promotion of BR investment on corporate performance.